Improving cellulosic ethanol production using ozonolysis and acid as a sugarcane biomass pretreatment in mild conditions - Perrone, Olavo Micali [UNESP]; Moretti, Marcia Maria de Souza [UNESP]; Bordignon, Sidnei Emilio [UNESP]; Pereira, Josiani de Cassia [UNESP]; da Silva, Roberto [UNESP]; Gomes, Eleni [UNESP]; Boscolo, Mauricio [UNESP] (Elsevier, 2021)
The efficiency of unpressurized ozonolysis (O) and acid washing (A) was investigated as a simple pretreatment procedure to depolymerize sugarcane biomass for posterior enzymatic hydrolysis and alcoholic fermentation to improve cellulosic ethanol production. The fiber chemical compositional analyses showed that the ozonolysis reduces the lignin content by 25%. High-performance anion-exchange chromatography (HPAEC-PAD) analysis showed that the loss of glucose during treatment was less than 1.5%. After enzymatic hydrolysis, the maximum glucose and xylose yield (310 ± 2 and 122 ± 3 mg g−1, respectively) were achieved from the OA treatment sequence and the fermentation yield was three times more ethanol than the yield from untreated bagasse. This simple treatment may be an alternative for improving cellulosic ethanol production using a mild-operational strategy.
Keywords: Biomass deconstruction; Enzymatic hydrolysis; Fermentation process; Ozonolysis